Faktor Risiko yang Mempengaruhi Terjadinya Stroke Non Hemoragik pada Pasien di RS RK Charitas dan RS Myria Palembang - Bangun Dwi Hardika; M Yuwono; HM Zulkarnain (Jurnal Akademika Baiturrahim Jambi, 2020)
Non-hemorrhagic stroke is a frequent case of stroke caused by blockage of blood vessels and the accumulation of changeable and unchangeable risk factors. The impact of stroke is a long-term physical and functional disorder that affects the life quality of the patient and the family. The aim of this study was to analyze the factors that influence the occurrence of non-hemorrhagic stroke. This study is an observational analytic epidemiological study with case control research design conducted in 2 private hospitals. The samples were selected sequentially with a ratio of 1: 2 (case: control) consisting of 50 patients with non-hemorrhagic stroke and 100 patients without non-hemorrhagic stroke. The data was analyzed by univariate, bivariate, and multivariate analysis method by using binary logistic regression. The results of risk factor analysis which were independently associated were Total Blood Cholesterol, History of Hypertension, Systolic Blood Pressure, Diastolic Blood Pressure, and Cardiac Examination. The multivariate analysis showed that the risk factors affecting non hemorrhagic stroke were History of Hypertension (OR: 6,476, p = 0.000, 95% CI: 2,338-17,935), Total Blood Cholesterol Level ≥200 mg/dl (OR: 6,139, p = 0.000, 95% CI: 2,334-16,148), Education Level (OR: 0,311, p = 0.009, 95% CI: 0,129-0,747), Gender (OR: 0.379, p = 0.022, 95% CI: 0.165-0.871 ), and Obesity (OR: 2,217, p = 0.080, 95% CI: 0.910-5.401). As a conclusion, there were 5 variables of risk factors that influence to Non Hemorrhagic Stroke. If those variables of risk factors were exist in the respondent, the risk of a non hemorrhagic Stroke reached 81.6%. It was suggested that the patients made an effort on preventions by maintaining a healthy lifestyle and controlling risk factors affecting the occurrence of non-hemorrhagic stroke.